The Influence of Total Quality Management, Competitive Advantage, and Leadership in Improving Operational Performance (Empirical Study of PT Roda Mas Baja Inti - Nurul Hikma Aljazirah, (Study of Scientific and Behavioral Management, 2024)
This research aims to examine the influence of Total Quality Management (TQM), competitive advantage, and leadership on improving operational performance at PT Roda Mas Baja. The approach used in this research is quantitative using SmartPLS version 4.0 analysis. The sample for this research consisted of employees of PT Roda Mas Baja. The results of the analysis show that TQM has a significant positive effect on operational performance, indicating that implementing effective TQM practices can increase company efficiency and productivity. Competitive advantage was also found to have a significant positive influence on operational performance, meaning that strategies that increase a company's competitiveness contribute to increased performance. Apart from that, effective leadership has been proven to play an important role in motivating and directing employees so that the implementation of TQM in the company runs well so that it can improve operational performance. Overall, the findings of this research confirm the importance of synergy between TQM, competitive advantage, and leadership in efforts to improve a company's operational performance. The practical implication of this research is the need for PT Roda Mas Baja management to continue to develop and implement strategies related to TQM, competitive advantage and leadership in order to achieve optimal operational performance.